ANALISIS PERDAGANGAN PRODUK ALAS KAKI INDONESIA - CHINA - Ragimun, Ragimun (Badan kebijakan Fiskal, 2012)
The Government continues to encourage non-oil exports in order to increase state revenues. One of them is a footwear product. Main export products are in addition to generating foreign exchange also employment. One factor that may affect the export of footwear products are competitive and many competitors' products, including China. Indonesia has the footwear of competitiveness is quite good for the world and exports of footwear products to China. From 2001 to 2010 Revealed Comparative Advantage (RCA) showed an average of over 1. Besides, the analysis of trade specialization index also shows the average above 0.5 which means that Indonesia is best suited as an exporter of footwear products. Related to this strategy of increasing competitiveness of footwear products, which need do is to continuously improve product quality and efficiency as well as footwear business climate in Indonesia.